The effect of dark chocolate on metabolism and performance in trained cyclists at simulated altitude - Shaw, K. A. (University of Saskatchewan, College of Kinesiology, 2019)
Dark chocolate (DC) is high in flavonoids, a bioactive micronutrient that increases the synthesis of nitric oxide (NO) and reduces the rate at which NO is removed from the blood. Nitric oxide is a potent vasodilator and its increase has potential to improve blood flow, delivery of oxygen to muscle, and endurance exercise performance, especially in conditions such as altitude, where hypoxia compromises delivery of oxygen to muscle. The purpose of this research was to investigate the effects of DC on cycling performance, metabolism, and blood oxygenation status in trained cyclists at altitude. We hypothesized that DC would result in enhanced muscular oxygenation, more efficient exercise metabolism, and improved performance. Twelve trained cyclists (n=2 females, average VO2 peak=54.6±6.2 ml/kg/min) were randomized to supplement with 60g of DC or an isocaloric placebo twice per day for 14 days in a cross-over study. After the 2-weeks of supplementation, participants attended a lab session in which they cycled 90 minutes at 60% VO2max followed immediately by a 10km time trial (TT) at a simulated altitude of 2500m (15% O2). Plasma levels of blood glucose and lactate were measured before, throughout, and after exercise while muscular and pre-frontal cortex oxygenation were measured continuously throughout exercise by near infrared spectroscopy. DC resulted in improved maintenance of blood glucose throughout the experimental trial (5.9±0.5 vs. 5.6±0.5 mmol/L; p=0.03) and decreased blood lactate following the time trial (7.7 mmol/L vs. 10.0 mmol/L, p=.027). DC had no effect on time trial performance (1142±129 vs. 1152±118 s for placebo) or oxygenation status in either the brain or muscle. There was an increase in total hemoglobin and deoxygenated hemoglobin in the pre-frontal cortex, and an increase in total hemoglobin in the vastus lateralis over time. Consumption of DC for two weeks prior to a bout of cycling at simulated altitude allows for maintenance of blood glucose during exercise and decreased lactate production following intense and prolonged TT but does not improve TT performance. Dark chocolate had no effect on oxygenation status of the pre-frontal cortex or working muscles.